2019
DOI: 10.1016/j.apenergy.2019.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous biomethanisation of endogenous and imported CO2 in organically loaded anaerobic digesters

Abstract: In-situ biomethanisation reduces the CO2 in biogas to CH4 via direct H2 injection into an anaerobic digester, but volumetric methane production (VMP) is limited by organic loading. Ex-situ biomethanisation, where gaseous substrates are fed to pure or mixed cultures of hydrogenotrophic methanogens, offers higher VMP but requires an additional reactor and supply of essential nutrients. This work combined the two approaches in a novel hybrid application achieving simultaneous in-situ and ex-situ biomethanisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…Although our positive control indicated assay specificity, we were unable to detect Methanococcus in the available salt marsh samples, possibly due to low microbial abundance resulting in DNA concentrations below the sensitivity of our LAMP assay. Consistent with 16S rRNA amplicon sequencing [5], Methanococcus was not detected by LAMP in mesophilic lab scale digesters (Figure 5c, lanes 4, 5). Using DNA extracted from stool samples from human volunteers, we confirmed the presence of Methanobrevibacter by LAMP.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Although our positive control indicated assay specificity, we were unable to detect Methanococcus in the available salt marsh samples, possibly due to low microbial abundance resulting in DNA concentrations below the sensitivity of our LAMP assay. Consistent with 16S rRNA amplicon sequencing [5], Methanococcus was not detected by LAMP in mesophilic lab scale digesters (Figure 5c, lanes 4, 5). Using DNA extracted from stool samples from human volunteers, we confirmed the presence of Methanobrevibacter by LAMP.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, our LAMP assay results are consistent with 16S rRNA amplicon profiles obtained for these samples in our previous work. We showed that CO 2 reductive biomethanisation systems were dominated by Methanoculleus genus hydrogenotrophs and that the abundance of these species increased with a rise in H 2 addition to these systems [5].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The so-called "catalytic" methanation, based on the Sabatier reaction, is carried out using chemical catalysts such as nickel at high temperatures (250-450 • C) [6,7]. The biological methanation (also called biomethanation) is based on microorganisms, the conversion being operated at moderate temperatures and pressures • C and atmospheric pressure up to 10 bars, respectively) [8][9][10]. In addition, when performed on biogas issued from anaerobic digestion (AD) plants, biological methanation can be considered as a substitute of a CO 2 purifier through biogas upgrading [7,11].…”
Section: Introductionmentioning
confidence: 99%